2018
DOI: 10.1038/s41467-018-05805-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupling reveals a novel therapeutic opportunity for p53-defective cancers

Abstract: There are considerable challenges in directly targeting the mutant p53 protein, given the large heterogeneity of p53 mutations in the clinic. An alternative approach is to exploit the altered fitness of cells imposed by loss-of-wild-type p53. Here we identify niclosamide through a HTS screen for compounds selectively killing p53-deficient cells. Niclosamide impairs the growth of p53-deficient cells and of p53 mutant patient-derived ovarian xenografts. Metabolome profiling reveals that niclosamide induces mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 54 publications
5
66
0
Order By: Relevance
“…The main arguments in favor of Mitchell's chemiosmotic theory were based on the ability of uncouplers to cause the collapse of the membrane potential by carrying protons across membranes. At present, there is a revival of interest in uncouplers because of the growing evidence of their broad-spectrum therapeutic efficacy [1][2][3][4][5][6][7][8][9], including antibacterial potency [10][11][12][13][14][15][16][17][18][19], which was actually found very early [20]. To this end, a series of esters of fluorescein were obtained and studied at our laboratory, manifesting themselves as rather effective mitochondrial uncouplers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The main arguments in favor of Mitchell's chemiosmotic theory were based on the ability of uncouplers to cause the collapse of the membrane potential by carrying protons across membranes. At present, there is a revival of interest in uncouplers because of the growing evidence of their broad-spectrum therapeutic efficacy [1][2][3][4][5][6][7][8][9], including antibacterial potency [10][11][12][13][14][15][16][17][18][19], which was actually found very early [20]. To this end, a series of esters of fluorescein were obtained and studied at our laboratory, manifesting themselves as rather effective mitochondrial uncouplers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Next, to investigate the biological functions of hub genes, GSVA was performed. Both P53 and hypoxia pathways have important roles in tumor survival and recurrence [31][32][33]. The above results showed that these four core genes were mostly related to the P53 and hypoxia signaling pathways.…”
Section: Discussionmentioning
confidence: 69%
“…mitochondria.This is consistent with the view that niclosamide partially mediates cell death through arachidonic acid. Interestingly, AA has been found to increase mitochondrial permeability transition (PT) and cytochrome c release [13].…”
Section: Discussionmentioning
confidence: 99%